TRADITIONAL AND UNCONVENTIONAL EDUCATION TECHNOLOGIES - S.T.Qosimova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Education in the process innovative education of technologies interactive of the methods when used , study of recipients activity increases and study to training has been interest more increases , communication get in skills is formed and passable to the topic positive in relation will be Teacher education in the process education methods when using , first of all , this from the method of use place , his efficiency to know important Of this for every one pedagogue vital to the experience have is enough knowledge with armed , education to recipients relatively of problems the solution in advance can solve and them education to recipients deliver qualification have to be it is necessary